Young Children Understand the Role of Agreement in Establishing Arbitrary Norms—But Unanimity Is Key. Issue 2 (17th March 2016) - Schmidt, Marco F. H.; Rakoczy, Hannes; Mietzsch, Teresa; Tomasello, Michael
Abstract : Human cultural groups value conformity to arbitrary norms (e.g., rituals, games) that are the result of collective "agreement." Ninety‐six 3‐year‐olds had the opportunity to agree upon arbitrary norms with puppets. Results revealed that children normatively enforced these novel norms only on a deviator who had actually entered into the agreement (not on dissenting or ignorant individuals). Interestingly, any dissent during the norm‐setting process (even if a majority of 90% preferred one course of action) prevented children from seeing a norm as established for anyone at all. These findings suggest that even young children understand something of the role of agreement in establishing mutually binding social norms, but that their notion of norm formation may be confined to conditions of unanimity.